Factors affecting the outcomes of tirofiban after endovascular treatment in acute ischemic stroke: Experience from a single center. (4th January 2023) - Wang, Yuan; Ma, Hongrui; Zhang, Qihan; Jin, Feiyang; Xu, Yi; Ma, Qingfeng; Ji, Xunming
Abstract: Aims: To investigate the predicted factors influencing the outcomes in acute ischemic stroke (AIS) patients who received tirofiban after endovascular treatment (EVT) and the optimal administration of tirofiban. Methods: In this retrospective study, AIS patients who received EVT followed by tirofiban between January 2017 and October 2021 were enrolled. The dose and duration of tirofiban were adjusted by trained clinicians according to the patient's clinical status. A reduction of at least four points on the National Institutes of Health Stroke Scale (NIHSS) after tirofiban compared with that before tirofiban was defined as an effective response. A modified ranking scale (mRS) of 0–2 was defined as a favorable outcome at a 90‐day follow‐up. Results: A total of 260 consecutive patients were enrolled, and 36.5% of patients achieved a favorable outcome. The modified thrombolysis in cerebral infarction (mTICI) 2b‐3 occurred in 93.5% of patients. Symptomatic intracerebral hemorrhage (sICH) occurred in 6.2% of patients, and the mortality at 90‐day follow‐up was 16.9%. Duration of tirofiban >24 h (adjusted OR: 2.545; 95% CI: 1.008–6.423; p  = 0.048) and effective response to tirofiban (adjusted OR: 25.562; 95% CI: 9.794–66.715; p  < 0.001) were related to the favorable outcome (mRS 0–2). Higher NIHSS (adjusted OR: 0.855; 95% CI: 0.809–0.904; p  < 0.001) and glucose level on admission (adjusted OR: 0.843; 95% CI: 0.731–0.971; p  = 0.018) were predictive for the unfavorable outcome (mRS 3–6). Conclusions: An effective response to tirofiban is an independent factor in predicting the long‐term efficacy outcome, and extending the duration of tirofiban is beneficial for neurological improvement. Abstract : An effective response to tirofiban is an independent predictor for neurological function independence at 90 days. Increased admission NIHSS and glucose level may adversely affect the outcome of EVT combined with tirofiban. The optimal duration of tirofiban treatment to achieve a good neurological outcome was 36 h.